Possible Role of Court-Type Thai Traditional Massage During Parturition: a Randomized Controlled Trial - Sananpanichkul, MD, Panya; Sawadhichai, MD, PhD, Chatchai; Leaungsomnapa, PhD, Yosapon; Yapanya, BATM, Paweena (International Journal of Therapeutic Massage & Bodywork, 2019)
Background and Objectives: Court-type Thai traditional Massage (c-TTM) applied during intrapartum may have some benefit other than pain relief. This study aimed to evaluate the effect of c-TTM during the first and second stage of labor, as well as pain alleviation in the first stage. Methods: This was a randomized controlled trial study. Eligible participants were singleton pregnant mothers with cervical dilation between 3–5 cm and no medical complications. Both trial groups received the same routine antepartum care except for 1 hour additional c-TTM given to the experimental group when they were in the active phase of labor. The pain score was taken from the participants at the time before labor pains started, at the time of active labor, 1, 2, 3, and 4 hours after the intervention. Pain was recorded by the researcher using a visual analog scale. The primary outcome during the first and second stages of labor was compared between groups. Pain relief during the first stage of labor and analgesic drugs used were compared as a secondary outcome. This trial is registered under the identification number TCTR20171115003. Results: Fifty-nine participants were enrolled and randomly assigned with 1:1 allocation to groups. The duration of first and second stage labor was significantly shorter in the experimental c-TTM than in the conventional control group (mean ± SD: 198.37 ± 62.80 minutes: 268.52 ± 137.81 minutes, p value =.02 and 17.54 ± 9.49 minutes: 23.35 ± 15.01 minutes, p value =.03, re-spectively). There was no difference of pain score between the groups. Conclusion: One hour of c-TTM can signifi-cantly decrease the duration of the first and second stages of labor. The pain score recorded is not statistically different between the groups.